2022
DOI: 10.1097/bot.0000000000002251
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Surgery Does Not Reduce Transfusion Rates in Low-Energy Hip Fractures on Direct Oral Anticoagulants

Abstract: Objectives: To compare transfusion rates in patients on direct oral anticoagulants (DOACs) with nonanticoagulated patients undergoing hip fracture surgery and, secondarily, to determine whether time to surgery or complications differ between these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
(66 reference statements)
1
17
0
Order By: Relevance
“…Multiple recent studies challenge this idea, with no difference found in transfusion rates and postsurgical hemoglobin changes between patients on DOACs and propensity-matched, uncoagulated cohorts. 30-33 We conclude that there is little evidence supporting routine delay for hip fracture fixation because of DOACs. Based on these studies, the harm from delaying surgery >24 to 48 hours may be greater than the risk of increased perisurgical bleeding from DOAC therapy.…”
Section: Intraoperative Managementmentioning
confidence: 78%
“…Multiple recent studies challenge this idea, with no difference found in transfusion rates and postsurgical hemoglobin changes between patients on DOACs and propensity-matched, uncoagulated cohorts. 30-33 We conclude that there is little evidence supporting routine delay for hip fracture fixation because of DOACs. Based on these studies, the harm from delaying surgery >24 to 48 hours may be greater than the risk of increased perisurgical bleeding from DOAC therapy.…”
Section: Intraoperative Managementmentioning
confidence: 78%
“…Our results contribute to a growing body of literature suggesting that DOACs do not meaningfully increase blood loss in this patient population. 11 This is particularly important for these drugs that can have relatively long half-lives and high-cost reversal agents with limited availability. 24 Importantly, the length of stay in this group did not differ from patients not taking anticoagulants, implying that blood loss in this group was not artificially depressed by delaying surgery until the effect of these medications had worn off.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented support a growing literature that surgical intervention for extracapsular geriatric hip fractures should not be delayed for patients taking anticoagulants. 11,17 Surprisingly, antiplatelet drugs including aspirin were more strongly associated with increased blood loss than anticoagulants. Because the increased blood loss from antiplatelet medications did not increase early postoperative mortality and anticoagulants did not meaningfully increase blood loss, early hip fracture fixation for patients taking anticoagulant drugs without reversal may be warranted to avoid the known risks of surgical delay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9] However, delayed surgery has not been shown to decrease transfusion rates, bleeding, or complications. 3,5,10,11 Recently published guidelines for patients with atrial fibrillation receiving factor Xa inhibitors recommend waiting 48 hours after the last dose to undergo surgery with high bleeding risk (eg, hip fracture surgery) to minimize blood loss. 12 However, the study does not provide recommendations for patients with decreased renal function because factor Xa inhibitors are renally cleared.…”
Section: Introductionmentioning
confidence: 99%